2016
DOI: 10.1017/sjp.2016.6
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Validation of the Basic Psychological Needs in Physical Education Scale between Portugal and Brazil Samples

Abstract: The main propose of this study is the cross-cultural validation of the Basic Psychological Needs in Physical Education Scale among Portugal and Brazil samples, through the study of measurement model invariance. Participated in this study, two independent samples, one with 616 Portuguese students, of the 2nd and 3rd basic grade of public school, aged between 9 and 18 years old and another with 450 Brazilian students, from 1st, 2nd and 3rd middle grade of public and private school, aged between 14 and 18 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 33 publications
1
11
0
7
Order By: Relevance
“…Similar results were found in the exercise context, (Vlachopulos et al, 2013), in physical education (Cid et al, 2016) and among genders in several studies (e.g., Vlachopoulos, 2008). These results reveal not only the quality of this measurement model in the evaluation of the three basic psychological needs, but also support what Deci and Ryan (2000) have said, which is that the basic psychological needs are innate and universal to human beings, whatever gender, ethnicity or cultural repertoire.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar results were found in the exercise context, (Vlachopulos et al, 2013), in physical education (Cid et al, 2016) and among genders in several studies (e.g., Vlachopoulos, 2008). These results reveal not only the quality of this measurement model in the evaluation of the three basic psychological needs, but also support what Deci and Ryan (2000) have said, which is that the basic psychological needs are innate and universal to human beings, whatever gender, ethnicity or cultural repertoire.…”
Section: Discussionsupporting
confidence: 85%
“…This supports using the measurement model in different cultures, for which the scientific evidence was posteriorly confirmed in a transcultural study regarding the invariances of the measurement model of the BPNES between Greece, Turkey, Spain and Portugal (Vlachopoulos et al, 2013). Further, the Portuguese version of the BPNESp was also adapted and validated preliminary for the physical education context (Pires, Cid, Borrego, Alves, & Silva, 2010), whose model was confirmed in a transcultural study between Portugal and Brazil, where it supported the adequacy of the measurement model for these two countries, as well as their invariance (Cid et al, 2016). In addition to this evidence, some multi-sample studies over the past few years have shown that the basic psychological needs are equivalent across gender, i.e.…”
Section: Introductionmentioning
confidence: 65%
“…The Basic Psychological Need in Exercise Scale Portuguese version [28] was employed to measure the extent to which participants felt that their needs were met during classes. This 15-item (5 items each factor) examines autonomy ("I feel that I can complete task in the way that I prefer"), competence ("I believe that I can complete personal challenges") and relatedness ("I feel that I get along well with others when I engage in the activities with others") satisfaction.…”
Section: Basic Psychological Needsmentioning
confidence: 99%
“…No contexto desportivo, as pesquisas que analisaram a invariância entre brasileiros e portugueses são ainda mais escassas. Entretanto, com base na TAD, ficou comprovada a invariância das necessidades psicológicas básicas entre estudantes para as aulas de educação física nos dois países (Cid et al, 2016). De uma maneira geral, ainda que reduzido os estudos que testaram a invariância entre brasileiros e portugueses, as pesquisas demonstram não ser frequente a invariância, como encontrada no presente estudo.…”
Section: Procedimentos De Recolha Dos Dadosunclassified